2007
DOI: 10.1111/j.1532-7078.2007.tb00242.x
|View full text |Cite
|
Sign up to set email alerts
|

A New Perspective on Neonatal Smiling: Differences Between the Judgments of Expert Coders and Naive Observers

Abstract: To better understand the form and recognizability of neonatal smiling, 32 newborns (14 girls; M = 25.6 hr) were videorecorded in the behavioral states of alertness, drowsiness, active sleep, and quiet sleep. Baby Facial Action Coding System coding of both lip corner raising (simple or non-Duchenne) and lip corner raising with cheek raising (Duchenne smile) was followed by a smile recognition task using 48 naive observers. Both types of smiles were detected in all behavioral states. Lip corner raising with chee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Since as early as the 13th week of gestation and neonatal period, smiles and other expressions are extremely common, especially during active REM sleep (Dondi et al 2007;Emde and Koenig 1969;Messinger et al 2002). The recent work of Messinger and collaborators showed that neonatal smiles, in particular Duchenne smiles that involve cheek raising and index positive emotion (Ekman 1992), are more frequent, stable, and enduring during active sleep (corresponding to adult REM sleep, Roffwarg et al 1966) than during other behavioral states (Dondi et al 2007;Messinger and Fogel 2007) (Fig. 2).…”
Section: Emotional Maturationmentioning
confidence: 99%
See 1 more Smart Citation
“…Since as early as the 13th week of gestation and neonatal period, smiles and other expressions are extremely common, especially during active REM sleep (Dondi et al 2007;Emde and Koenig 1969;Messinger et al 2002). The recent work of Messinger and collaborators showed that neonatal smiles, in particular Duchenne smiles that involve cheek raising and index positive emotion (Ekman 1992), are more frequent, stable, and enduring during active sleep (corresponding to adult REM sleep, Roffwarg et al 1966) than during other behavioral states (Dondi et al 2007;Messinger and Fogel 2007) (Fig. 2).…”
Section: Emotional Maturationmentioning
confidence: 99%
“…These authors put forward the interesting hypothesis that such smiles could relate to the activation of the amygdala and limbic structures during REM sleep (see Sect. 2 above), and may foster the functional coordination of facial motor programs with neural structures supporting the emotional and social expression of smiling later in development (at about 2 months of age) (Dondi et al 2007).…”
Section: Emotional Maturationmentioning
confidence: 99%
“…Finally, it has been proposed that off-line emotional maturation takes place during Rapid eye movement (REM) sleep since as early as the 13th week of gestation (Kurjak et al, 2005; Dondi et al, 2007) and that quiet sleep of human neonates contributes to the formation of cortical connections required for sensorimotor coordination and body representation (Milh et al, 2007). Overall, sleep seems necessary for the genesis of consciousness and self-awareness via the interaction of genetic instructions with off-line sleep-dependent perceptual experiences (Hobson, 2009; Perogamvros, 2012).…”
Section: The Dreaming Brain As An “Endogenous” Morel's Machine and Itmentioning
confidence: 99%
“…Stating this explicitly, Xu and Spelke wrote “the capacities to represent approximate numerosity found in adult animals and humans … develop in human infants” (p. B1). However, other researchers (Allen & Bickhard, in press; Simon, 1997) have argued that what can appear in infants to be adult‐like competence in the number domain might in fact be something quite different, much as smiling in human neonates looks like smiling in adults even though these are widely regarded as being two very different kinds of responses (Dondi et al, 2007; Messinger & Fogel, 2007).…”
Section: The Potential Utility Of Homology Thinking For Developmentalmentioning
confidence: 99%